Molecular mechanisms of inhibiting glucosyltransferases for biofilm formation in Streptococcus mutans - Zhang, Qiong; Ma, Qizhao; Wang, Yan; Wu, Hui; Zou, Jing (International journal of oral science, 2021)
Glucosyltransferases (Gtfs) play critical roles in the etiology and pathogenesis of Streptococcus mutans (S. mutans)- mediated dental caries including early childhood caries. Gtfs enhance the biofilm formation and promotes colonization of cariogenic bacteria by generating biofilm extracellular polysaccharides (EPSs), the key virulence property in the cariogenic process. Therefore, Gtfs have become an appealing target for effective therapeutic interventions that inhibit cariogenic biofilms. Importantly, targeting Gtfs selectively impairs the S. mutans virulence without affecting S. mutans existence or the existence of other species in the oral cavity. Over the past decade, numerous Gtfs inhibitory molecules have been identified, mainly including natural and synthetic compounds and their derivatives, antibodies, and metal ions. These therapeutic agents exert their inhibitory role in inhibiting the expression gtf genes and the activities and secretion of Gtfs enzymes with a wide range of sensitivity and effectiveness. Understanding molecular mechanisms of inhibiting Gtfs will contribute to instructing drug combination strategies, which is more effective for inhibiting Gtfs than one drug or class of drugs. This review highlights our current understanding of Gtfs activities and their potential utility, and discusses challenges and opportunities for future exploration of Gtfs as a therapeutic target.